THE LEFT VENTRICLE DIASTOLIC FUNCTION IN PATIENTS WITH HYPERTENSION UNDER THE USE OF DIFFERENT DRUG GROUPS - A. V. Budnevskij; E. S. Ovsjannikov; L. E. Kulikova (SINAPS LLC, 2019)
The objective: To assess the prevalence of diastolic dysfunction in patients with hypertension and preserved left ventricular ejection fraction under pharmacological correction (monotherapy) with angiotensin converting enzyme inhibitors, angiotensin II receptor blockers and β-blockers. Materials and methods: 82 patients (58 women and 24 men) with stage 2 hypertension were examined. The diastolic function was assessed via echocardiography in accordance with the European Association of Cardiovascular Imaging guidelines (2017). Echocardiography was performed before the onset of the treatment and 6 months after its onset. The treatment onset was considered to start after a 2-week period of elimination of previously used pharmacological substance and 2 weeks of assessing tolerability, dose and regimen adjustment. Results: For all selected drugs, target values of blood pressure were achieved, and no adverse effects were identified. The average values of the left atrial volume index before and after the treatment course did not show significant differences. In the majority of the examined patients, this parameter did not exceed the threshold value of 34 ml/m2 . Values exceeding the specified threshold were observed in Group 1 in 4 patients, in Group 2 in 3 patients and in Group 3 in 8 patients. According to the Tissue Doppler echocardiography results on the velocity of myocardial motion at the early diastolic filling, which was measured at the level of the lateral segments of mitral valve and the interventricular septum, positive, but unreliable changes were observed in the Groups of bisoprolol and valsartan, and no changes - in the Group of perindopril. According to the traditional criteria, diastolic dysfunction was observed in 80 % of patients, while according to the criteria of the European Association of Cardiovascular Imaging (2017) - in 21 % of patients. Conclusion: The same efficacy of all three drugs is observed in terms of achieving target blood pressure values. The most pronounced effect on the morphometric parameters of the left atrium and intracardiac hemodynamics is shown in the Groups of bisoprolol and valsartan.